Growth hormone reduces retinal inflammation and preserves microglial morphology after optic nerve crush in male rats - Balderas-Márquez, Jerusa E.; Epardo, David; Siqueiros-Márquez, Lourdes; Carranza, Martha; Luna, Maricela; Quintanar, José Luis; Arámburo, Carlos; Martínez-Moreno, Carlos G. (Frontiers in Cellular Neuroscience, 2025)
IntroductionThis study investigates the neuroprotective role of growth hormone (GH) in modulating retinal inflammation and microglial responses following optic nerve crush (ONC) in male rats.MethodsRetinal inflammation and microglial activation were assessed at 24 h and 14 days post-ONC, with or without GH treatment (0.5 mg/kg, subcutaneously, every 12 h). Gene and protein expression of inflammatory markers (e.g., IL-6, TNFα, Iba1, CD86, CD206) were evaluated using qPCR, ELISA, and Western blotting. Microglial morphology was quantified using skeleton and fractal analysis of Iba1-stained retinal sections. Retinal structure and function were assessed via fundus imaging and optomotor reflex testing.ResultsONC induced significant increases in proinflammatory cytokines (IL-6, TNFα, IL-18) and microglial activation, characterized by reduced branching complexity and increased cell density. GH treatment significantly decreased proinflammatory cytokine levels, modulated microglial phenotype (CD86/CD206 expression), and preserved microglial morphology in the retina. Using the SIM-A9 microglial cell line, we further demonstrated that GH reduces NFκB pathway activation and suppresses LPS-induced proinflammatory cytokine production. At 14 days post-injury, GH-treated retinas exhibited reduced optic nerve size and improved optomotor responses, indicating both structural neuroprotection and functional recovery.DiscussionOverall, GH mitigates ONC-induced retinal inflammation by reducing proinflammatory signaling and preserving microglial architecture, thereby protecting retinal integrity and function. These findings highlight the potential of GH as a therapeutic agent for retinal neurodegenerative conditions.